Effect of diets containing whole cottonseed on the quality of sheep semen - doi: 10.4025/actascianimsci.v34i3.12963 - Maria das Graças Gomes; Carmen Iara Mazzoni Gonzalez; Francisco Fernando Ramos de Carvalho; Adriana Trindade Soares (Acta Scientiarum. Animal Sciences, 2012)
This study evaluated the semen quality of Santa Ines sheep fed diets containing different levels of whole cottonseed (WCS). Twenty sheep were distributed into four groups that were given diets with 0; 20; 30; 40% of WCS. For this study the semen was collected by electroejaculation, and a monthly andrological examination was performed during nine months. The analyzed variables were: scrotal circumference (SC), appearance and color of the ejaculate, progressive motility (PM), vigor, mass movement (MM), total sperm concentration (spzX109), sperm morphology (SM) and blood hematocrit. The SC had no difference among diets, with mean 31.83 cm. The animals fed diets with WCS, presented mean intake of 9.16 mg gossypol kg BW, and were prone to present greenish semen, and appearance ranging from thin creamy to watery. The PM decreased linearly (p < 0.05) with increasing level of WCS, while the vigor had a quadratic trend. The total defects increased linearly in relation to reference values described in literature. The WSC had no influence on hematocrit levels, but did affect the PM and vigor of spermatozoa, thus not recommended to diets of animals for breeding.